Nitric Oxide/Protein Kinase G-Iα Promotes c-Src Activation, Proliferation and Chemoresistance in Ovarian Cancer - Fiscus, Ronald R.; Leung, Elaine L.; Wong, Janica C.; Johlfs, Mary G. (IntechOpen, 2012)
None